Urgensi Pembekalan Literasi Sains bagi Siswa MTs NU Jogoloyo Wonosalam Demak - Indah Budi Handayani; Muhammad Syaipul Hayat; Fenny Roshayanti (Action Research Journal, 2022)
The purpose of this study was to determine the urgency of scientific literacy for students of MTs NU Jogoloyo Wonosalam Demak based on current conditions. This study uses a quantitative descriptive research design, namely research that aims to describe the urgency of students' scientific literacy achievements. The sample of this research is grade IX students at MTs NU Jogoloyo which is determined by total sampling technique. The research instrument was in the form of a scientific literacy test consisting of 20 multiple choice questions from the competence domain and the knowledge domain. Data retrieval is done by giving science literacy test questions to students and then processed by calculating the percentage of achievement for each literacy subdomain. The results showed that in general the scientific literacy ability of MTs NU Jogoloyo students in all subdomains was relatively low, even some subdomains were very low. So it can be concluded that scientific literacy is very important to provide students at MTs NU Jogoloyo Wonosalam Demak.